Chest X-ray-confirmed pneumonia in children in Fiji - H.C. Magree; F.M. Russell; R. Sa'aga; P. Greenwood; L. Tikoduadua; J. Pryor; L. Waqatakirewa; J.R. Carapetis; E.K. Mulholland (Bulletin of the World Health Organization, 2005)
OBJECTIVE: To calculate the incidence and document the clinical features of chest X-ray- (CXR-) confirmed pneumonia in children aged between 1 month and 5 years living in Greater Suva, Fiji. METHODS: A retrospective review was undertaken of children aged between 1 month and 5 years with a discharge diagnosis suggesting a lower respiratory tract infection (LRTI) admitted to the Colonial War Memorial Hospital in Suva, Fiji, in the first 10 days of each month from 1 January 2001 to 31 December 2002. Clinical data were collected and CXRs were reread and classified according to WHO standardized criteria for CXR-confirmed pneumonia. FINDINGS: Two hundred and forty-eight children with LRTI met the inclusion criteria. CXRs were obtained for 174 (70%) of these cases, of which 59 (34%) had CXR-confirmed pneumonia. The annual incidence of CXR-confirmed pneumonia was 428 cases per 100 000 children aged between 1 month and 5 years living in Greater Suva. If a similar proportion of the children for whom CXRs were unavailable were assumed to have CXR-confirmed pneumonia, the incidence was 607 per 100 000. The incidence appeared to be higher in Melanesian Fijian than Indo-Fijian children. The case-fatality rate was 2.8% in all children with LRTI, and 6.8% in those with CXR-confirmed pneumonia. CONCLUSION: This is the first study to document the incidence of CXR-confirmed pneumonia in a Pacific Island country, and demonstrates a high incidence. A significant proportion of hospital admissions of children with LRTI are likely to be preventable by the introduction of pneumococcal conjugate vaccine.